Toward a Resilient Islamic Banking System: Insights from 14 Years of Research - Wiranatakusuma, Dimas Bagus; Aprizal, Anggi; Yusof, Rosylin Mohd; Primambudi, Ganjar; Wahab, Norazlina Abd; binti Abdul Majid, Nurul Huda; Arundaya, Faiz Ajhar (ETIKONOMI, 2025)
Research Originality: This research is unique in that it consolidates macroeconomic and institutional studies to better understand how Islamic banks absorb and recover from financial shocks. Research Objectives: To investigate the conceptual and empirical development of Islamic banking resilience over the past 14 years, concentrating on dominating variables and thematic clusters. Research Method: The research examines 42 peer-reviewed journal articles indexed in Scopus through a comprehensive systematic literature review (SLR) methodology utilizing bibliometric instruments. Empirical Results: Internal factors like capital adequacy, liquidity, and profitability, as well as macroeconomic indices like GDP and inflation, influence resilience. The keyword “bank resilience” is underused, implying a lack of conceptual consistency in the literature. JEL Classification: G21, G32, E44, E58, Z12 Implications: An integrated view of resilience in Islamic finance and the requirement for specialized regulatory frameworks and resilience-based performance metrics customized to Islamic banking principles has substantial implications for researchers, policymakers, and regulators.